A novel method to promote selective oxidation of Ni-Cr alloys: Surface spreading α-Al2O3 nanoparticles. (September 2021) - Xie, Yun; Huang, Yuanchao; Li, Yihang; Peng, Xiao
Highlights: The bare Ni-10Cr alloy had insufficient Cr to form an external chromia scale in air at 800 °C. The α-Al2 O3 coated Ni-10Cr alloy succeeded in external chromia formation. The α-Al2 O3 nanoparticles assisted nucleation and growth of Cr2 O3, as they share the similar hcp crystal structure. Abstract: Following Wagner's classical oxidation theory, we suppose that a Ni-Cr alloy with the Cr concentration below the critical N Cr 1 (0.24) required for external Cr2 O3 scale formation but above the critical N Cr ( 2 ) (0.1) required for its steady-state growth, would be converted from a NiO former to a Cr2 O3 former, if the selective Cr oxidation of the binary alloy can be catalyzed at the beginning of oxidation. As is expected, spreading α-Al2 O3 nanoparticles on the surface of Ni-10Cr (NCr = 0.11) does cause it to become a Cr2 O3 former during oxidation at 800 °C. The α-Al2 O3 effect on oxidation is interpreted.